Growth curves in beef cows of different biological types - Silva, Fabiane de Lima; de Alencar, Maurício Mello; de Freitas, Alfredo Ribeiro; Packer, Irineu Umberto; Mourão, Gerson Barreto (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this study was to select the best growth curve model, and to evaluate the influence of environmental and genetic group effects on the estimated parameters of the model. Five nonlinear models, Brody, Gompertz, Logistic, Von Bertalanffy and Richards, were adjusted to age‑weight data measured in 316 cows, obtained from four genetic groups: G (Nellore, ½Canchim + ½Nellore, ½Angus + ½Nellore, and ½Simmental + ½Nellore), from birth to 100 months of age; in two calving seasons: E (spring and fall). The cows were submitted to two levels of concentrate (S) during four months, after weaning. The models were adjusted by ordinary least squares using inverse‑variance weighted and unweighted mass. The Brody and Von Bertalanffy models converged for all genetic groups; however, the Brody model had a better fit. Estimates for asymptotic weight (A) and maturing rate (k) of the weighted Brody model were analyzed by a mixed model, which included overall effect and fixed effects of G, E, and S, and respective interactions. Parameter A was influenced by the effects of G and E, while k was influenced by S, indicating that improvements in feeding management result in less variation in the shape of growth curves and in increased rates of maturity.